Protein hydrolysates from agricultural wastes for plant bacterial disease control - Ditsawanon, T.; Parinthawong, N.; Phaonakrob, N.; Roytrakul, S. (My University, 2022)
Agricultural wastes, agro-industrial wastes and fishery wastes were collected and the protein hydrolysates were obtained with pepsin. Antibacterial activity of smaller than 3 kDa protein hydrolysates was determined against the plant pathogenic bacteria; Xanthomonas citri, Ralstonia solanacearum, Burkholderia cepacia and also against plant growth promoting rhizobacteria (PGPRs); Bacillus subtilis, Pseudomonas aeruginosa and P. fluorescens. Coconut residues (agro-industrial waste from coconut milk production), peanut seed coat (from peanut-based snack production) and rice straw (waste from rice farms) showed antimicrobial activity against X. citri, R. solanacearum and B. cepacia with higher than 74% inhibition. Coconut residue also increased growth of PGPRs, B. subtilis and P. fluorescens. Further protein hydrolysates from Nile tilapia (Oreochromis niloticus) and snake-head fish (Clarias batrachus) fin increased growth of all PGPRs.
Keywords: Agricultural wastes; Antimicrobial activity; Plant pathogenic bacteria; Protein hydrolysates